IMPLEMENTASI INTRUSION DETECTION SYSTEM MENGGUNAKAN ALGORITMA BLOWFISH Studi Kasus DI DOTA CAFE - Hasibuan, Doli; Naibaho, Jimmy Febrinus; Simanjuntak, Christian P (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2019)
Cryptography is the study of system security, where the system needs to be secured from interference or threats from irresponsible parties. In everyday life, fraud is often found in important data, one of which is cashier system data. To prevent and overcome this, the concept of network security with the Blowfish Algorithm will be applied. One of the cryptographic algorithms is the Blowfish Algorithm. The Blowfish algorithm is quite simple but strong enough because it has a long keyspace, making it difficult to attack. Unexpected things often occur such as foreign parties who want to enter the system by repeatedly trying the possible username and password, or foreign parties changing the data in the cash register at Dota CafÃ©. This system will function to monitor system activity, in this case if the system feels a threat or system disturbance is found.